Planet Earth: its physical systems through geologic time - Strahler, Arthur Newell (New York : Harper & Row Publishers, Inc., 1972)
This book is written to meet changing academic viewpoints as well as to induce further changes in response to demands by students, faculties and the informed public for a new set of priorities in science education and research. Two key words focus attention on these new standards of priority: unification and relevance. Both words suggest a need to reverse the long-term drift of natural science to a position and function no longer entirely acceptable to society.
Preface -- Prologue: Physical Systems of Planet Earth -- 1. Sun-Earth-Space Energy System: The Planetary Radiation Balance -- 2. Particle Flux System, Sun-Earth Space: Solar Wind and the Earth's Magnetic Field -- 3. Kinetic Energy System of Masses in Motion: Planets and Satellites -- 4. Transport Systems: I. Atmospheric-Oceanic Circulation and the Earth's Heat Balance -- 5. Transport Systems: II. Changes in State of Atmospheric Water -- 6. Transport Systems III. Gravity Flow of Water on the Lands -- 7. Geologic Systems: I. Radiogenic Heat and the Rise of Molten Rock -- 8. Exogenetic Processes and Products: I. Rock Transformation and Sediments -- 9. Exogenetic Processes and Products: II. Continental Denudation and Its Landforms -- 10. Geologic Systems: II. Radiogenic Heat and Diastrophism -- 11. Impact System, Space to Earth and Moon: The Geology of Planetary Space -- 12. Geogolic Systems Through Time: I. Origin and Early History of the Earth -- 13. Geologic Systems Through Time: II. Eras of Abundant Life--The Paleozoic Eras -- 14. Geologic Systems Through Time: II. Eras of Abundant Life--The Mesozoiic and Cenozoic Eras -- 15. Stellar Systems and Galactic Evolution: A Cosmology Beyond the Realm of Man -- Epilogue: Man as Agent of Change on Planet Earth -- Appendix: Cross-reference to Supplementary Publication -- Index.
Includes bibliographical references and index.
Keywords: EARTH SCIENCES